The prevalence and type of Axis-I and Axis-II mental disorders in subjects with non-specific chronic back pain: results from a population-based study - Gerhardt, Andreas; Hartmann, Mechthild; Schuller-Roma, Bärbel; Blumenstiel, Klaus; Bieber, Christiane; Eich, Wolfgang; Loos, Sabine (Pain medicine, 2011)
Objective. To investigate the prevalence and the type of mental comorbidity in a population-based sample of subjects with non-specific chronic back pain.Design. Representative population-based survey.Setting. The city of Heidelberg (in southwestern Germany) and 10 adjacent communities.Patients. From a random sample of individuals (N = 2,000), 1,091 subjects completed a questionnaire including a pain assessment. Of those, 188 subjects (17%) fulfilled the criteria for chronic back pain (≥45 days of back pain in the last 3 months) and were subsequently invited to undergo a detailed clinical examination; 131 subjects (70%) agreed to participate. The Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders IV (DSM-IV) (SCID-I + II) was used to assess current (defined as the previous 4 weeks) mental comorbidity and was completed in 110 subjects (84%) with non-specific chronic back pain.Intervention. N/A.Outcome Measures. DSM-IV mental comorbidity diagnoses.Results. The overall prevalence of mental comorbidity of Axis-I and -II disorders were 35.5% and 15.5%, respectively. Of Axis-I disorders, anxiety disorders (20.9%) and affective disorders (12.7%) were the most frequent. Of Axis-II disorders, 9.1% of diagnoses was of the Cluster C category (anxious/inhibited). Compared with the general population, the total rate of Axis-I comorbidity was significantly higher, while the total rate for Axis-II personality disorders was only slightly different.Conclusions. The consistent diagnoses of anxiety, fear, and avoidance in these subjects indicate that also primary care health professionals should consider anxiety disorders in patients with chronic pain, in addition to the affective disorders that are most frequently self-reported in pain patients.